2020
DOI: 10.15212/bioi-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Artificial Intelligence in Chest Imaging of COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) has infected more than 9.3 million people and has caused over 0.47 million deaths worldwide as of June 24, 2020. Chest imaging techniques including computed tomography and X-ray scans are indispensable tools in COVID-19 diagnosis and its management. The strong infectiousness of this disease brings a huge burden for radiologists. In order to overcome the difficulty and improve accuracy of the diagnosis, artificial intelligence (AI)-based imaging analysis methods are explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…In addition, to make a critical presentation, in the opinion of the authors of this work, of why most of this research leads to unreliable results. This is the main difference of our research with other review studies like [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] that analyze automatic classification of COVID-19 using CXR images, because none of them address the problems related to the lack of generalization reported in several papers [ 31 ]– [ 34 ].…”
Section: Introductionmentioning
confidence: 81%
“…In addition, to make a critical presentation, in the opinion of the authors of this work, of why most of this research leads to unreliable results. This is the main difference of our research with other review studies like [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] that analyze automatic classification of COVID-19 using CXR images, because none of them address the problems related to the lack of generalization reported in several papers [ 31 ]– [ 34 ].…”
Section: Introductionmentioning
confidence: 81%
“…Although LUS results are related to the degree of aeration of the lung’s outer and subpleural layers, they can effectively reflect the condition of lung involvement. Previous study has shown that most COVID-19 pneumonia cases present with peripulmonary and subpleural involvement in the early stage [ 20 ], and this pathological feature is easy to detect by ultrasound. These characteristics of COVID-19 pneumonia provide an ideal application condition for LUS.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have carried out investigations on both CT and X-ray image modalities for COVID and non-COVID classification and reported satisfying accuracy [59] , [60] , [61] . Many transfer learning models were analysed and fine-tuned for extracting features of COVID-19 infected chest X-ray and CT image in [62] , where the VGG-19 model gave out the best accuracy of 99%.…”
Section: Robotics and Ai Technologies In Covid-19 Healthcarementioning
confidence: 99%